Support from teachers and trainers in vocational education and training : the pathways to career aspirations and further career development - Hofmann, Claudia [Verfasser]; Stalder, Barbara E. [Verfasser]; Tschan, Franziska [Verfasser]; Häfeli, Kurt [Verfasser] (My University, 2014)
"Transition from school to work is a challenging period for young people with learning difficulties. In the dual vocational system of Switzerland, teachers at vocational educational and training (VET) schools, as well as trainers at VET companies, provide important support. We were interested in the different pathways from this support to apprentice's career aspirations and further training. Structural equation modelling was used to analyse data from a longitudinal study in four occupational sectors. Results show that VET teacher support is directly and indirectly related to career aspirations at the end of the apprenticeship, whereas VET trainer support influences career aspirations only indirectly. Domain specific constructs (ability self-concept at VET school, skill variety at the VET company) and self-esteem are important as intermediary variables. Ability self-concept at VET school had a strong influence on further education three years after the apprenticeship." (Authors' abstract, BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); G 1.3.3 Bildungs- & Erwerbsbiografien; I 2.2.1 Westeuropa; Berufseinmündung; Zweite Schwelle; Ausbildungsabsolvent; Lernschwierigkeit; Bildungspersonal; Einflussfaktor; Berufsverlauf; Weiterbildungsbeteiligung; Langzeitstudie; Schweiz